The “Stick-Slip” Phenomenon During the Active Earth Pressure Failure of a Granular Soil of Analogical Material - Daoud, S. M.; Meghachou, M.; Abbad, H.; Vacher, P. (Engineering, Technology & Applied Science Research, 2014)
The aim of this paper is to highlight the "stick-slip" phenomenon in the mechanisms of failure related to active earth pressure of an analogical material simulating a granular medium. For this, a two-dimensional small-scale model was used and a phenomenological analysis of these mechanisms was conducted employing measurements of the fields of deformations using the method of digital image correlation. It was noted that a fluctuation in the response of the material occurs during the equal increments of displacements imposed on the mobile wall. This incremental response of the medium during the failure process related to active earth pressure explains the "stick-slip" phenomenon